Constraint Loss Estimation Schemes In Deep And Shallow Three-Dimensional Crack Tip Fields - Karh Heng, Leong (2017)
The primary goal of this study is to determine the three-dimensional constraint loss behavior and further extend the three-dimensional constraint loss estimation schemes of